Neem Establishment in Arid Zone as Influenced by Different Techniques of Rain Water Harvesting - Gupta, G. N.; Choudhary, K. R.; Singh, Bilas; Mishra, A. K. (Indian Forester, 1993)
A field experiment was conducted to study the influence of different techniques of rain water harvesting on establishment of Neem (Azadirachta indica) at the research farm of Arid Forest Research Institute, Jodhpur. The various treatment were: Control, Weed removal (W.R.), Weed removal + Soil working (S.W.), W.R.+S.W. +Saucers of 1.0 m dia, W.R.+ S W.+Saucers of 15m dis, W. R. +S. W. +mulching in saucers around the plants, water conservation structuns in checker board design and water conservation structures as inter row slopes of 20 per cent. Out of the eight treatments, the inter row slopes of 20 per cent caused significantly higber moisture conservation in the root zone (40 per cent higher than the control) which resulted in better growth of neem (296 cm tall trees than 203 cm in control at ]8 month age). The treatment of weed removal alone caused tree heigbt improvement by 26 per cent over control. The weed removal helped conserving 20 per cent higher moisture than control. The practices of mulching and making saucers also improved the tree growth considerably. The coefficients of correlation between per cent increase in collar girth was 0.73 and with per cent increase in tree hight was 0.48.